التنغيم والقوانين النحوية - ربيح, عمار (Revues faculté des lettres et des langues, 2018)
Abstract: Grammar is a strict system of laws that govern the speaker’s performance. Not only grammatical rules set the functions for a defined and correct form of speech but, also some vocal functions such as tone and toning can be important determinants of functions and grammatical meanings. This article deals with the phenomenon of toning in Arabic and its impact on grammatical laws, and considers the change of some laws in response to the melody used by the speaker when uttering his words or sentences. الملخص النحو نظام صارم من القوانين التي تضبط أداء المتكلم ،وليست القواعد النحوية التي تضبط الوظائف وحدها المحدد لنموذج صحيح من الكلام ، بل أن بعض الأداءات الصوتية كالنبر و التنغيم يمكن أن تكون محددات مهمة للوظائف و المعاني النحوية و المقال يتناول ظاهرة التنغيم في العربية و أثرها على القوانين النحوية و ينظر في تغير بعض القوانين استجابة للنغم الذي يتلفظ به المتكلم  جملته .